EFFECTS OF MULTIMEDIA CONTENTS ON THE BRAIN DURING MEMORY RETENTION AND RECALLING PROCESS - HANOUNEH, SAMER (2017)
Including multimedia as a part of instruction can significantly enhance student learning. Therefore, understanding the effects of using multimedia on brain activities during memory recall can help to build better learning system which reflects increasing in memory performance for the learners. Few interesting previous studies investigated the effects of using multimedia subjectively as well as objectively but for short-term memory only, while long-term memory previous studies used only subjective measurement. Thus, this research focuses in investigating the effects of using multimedia on long-term memory using subjective feedback and EEG signals for objective measurement. Electroencephalogram (EEG) is an important neuroimaging modality which allows studying the changes in brain neuronal networks related to cognitive processes.